The Challenges to the Equal Parliamentary Representation of Women During the Electoral Process in Malawi - Dyani-Mhango, Ntombizozuko (University of Pretoria, 2023)
Mini Dissertation (Mphil (Multidisciplinary Human Rights))--University of Pretoria, 2022.